BODY MASS INDEX AND HEALTH RISK STATUS OF PHYSICAL EDUCATION STUDENTS, UNIVERSITY OF NIGERIA, NSUKKA - Aniodo, D. A.; Dibia, Samuel I.C.; Anike, Anthony I. (International Journal of Human Kinetics, Health and Education, 2023)
The study determined the body mass index and health risk status of Physical Education (PE) students, University of Nigeria, Nsukka. Three research questions and two null hypotheses guided the study. A descriptive survey design was adopted to assess Body Mass Index (BMI) and health risk status of PE undergraduates in University of Nigeria Nsukka. The population of the study consisted of all the PE students in University of Nigeria Nsukka. The entire population was used for the study because the population was manageable. In essence, there was no sampling procedure. The instruments for data collection were height scale, tensor metre scale. Questions were asked on age of the respondents orally. In data collection, height and weight were measured with standardized protocols and calibrated equipment in the departmental exercise physiology laboratory. Body Mass Index was calculated as weight in kilograms divided by height in metre squared and rounded to one decimal place. The information elicited on the ages were used to ascertain the health status of the students. Data analyzed were presented using descriptive statistics. The study showed that respondents have the tendency towards a healthy BMI and health status. The study recommended that more emphasis should be placed on nutrition education so as to educate the students on the basic dietary practices that are good. Efforts should be made also to uncover the consequences of poor dieting on the students and other groups of individuals.